Malaysian waqf efficiency (2010 – 2024): Concise evidence across operational, financial, and social lenses - Husin, Azrizal; Misbahrudin, Nor Tasik; Borhan, Nur Amirah; Yahaya, Rusliza (International Journal of Accounting, Finance and Business, 2025)
This mini-review synthesizes peer-reviewed evidence (2010–2024) on waqf efficiency in Malaysia across operational, financial, and social dimensions, based on a targeted search of Scopus Core Collection (last search: 01 November 2025), yielding eleven Malaysia-focused studies and four comparator pieces. Overall performance appears moderate but uneven: reporting timeliness is acceptable, yet quality and comparability vary across SIRCs; legal frictions in land registration/enforcement impede asset activation; and liquidity/accountability constraints weigh on financial sustainability, with only isolated cases meeting robust ratio-based thresholds. Responses include scaling cash waqf, exploration of waqf-linked sukuk, and digital platforms for fundraising/disclosure. Blockchain is frequently proposed for traceability and transparency, though Malaysian implementation evidence remains limited. Benchmarking Türkiye suggests gains from clearer statutory roles, professionalized trusteeship, and end-to-end digital reporting, subject to Malaysia’s federal–state context. We outline policy-proximal priorities—legal harmonization, concise integrated reporting (including ESG-aware metrics), and evidence-led fintech pilots—and present a focused research agenda on digital adoption effects, corporate vs traditional models, and state-level impact evaluations